The Analysis Of Honeypot Performance Using Grafana Loki And ELK Stack Visualization - Njoera, Yahya Alexander Djo; Hartawan, I Nyoman Buda; Ariana, Anak Agung Gede Bagus; Krisna, Evi Dwi (SEAN Institute, 2024)
Through the development of current technology, many agencies have implemented technology in the form of computers and servers to improve company operations. However, there are several aspects of threats in the form of cyber attacks that lurk someone when using a computer connected to the internet. One way to prevent these attacks is to use a honeypot application. Honeypot is a system used to deceive hackers who carry out cyber attacks on the system. Every attack received by the honeypot will be recorded in a log. However, reading log data from the honeypot is still difficult to do directly. So an application is needed that can visualize log data from the honeypot. In this study, the visualization applications used are Grafana Loki and ELK Stack. The purpose of this study was to determine the performance of Grafana Loki and ELK Stack in using system resources and in visualizing data. The results of this study indicate that Grafana Loki when processing or not processing honeypot log data uses less system resources compared to ELK Stack. ELK Stack uses 37.8% or 2930 MB of memory, while Grafana Loki only uses 9.7% or 769 MB. Although ELK Stack requires more CPU and memory resources, its data visualization is easier to do compared to Grafana Loki.